Hidden Chicano cinema : film dramas in the borderlands - Meléndez, A. Gabriel (Anthony Gabriel) (Latinidad: transnational cultures in the United States., 2013)
This book examines how New Mexico, situated within the boundaries of the United States, became a stand-in for the exotic non-western world that tourists, artists, scientists, and others sought to possess at the dawn of early filmmaking, a disposition stretching from the silent era to today as filmmakers screen their fantasies of what they wished the Southwest Borderlands to be. The book highlights "film moments" in this region's history including the "filmic turn" ushered in by Chicano/a filmmakers who created new ways to represent their community and region